Effects of PPARD gene variants on the therapeutic responses to exenatide in chinese patients with type 2 diabetes mellitus - Song, Jinfang; Li, Na; Hu, Ruonan; Yu, Yanan; Xu, Ke; Ling, Hongwei; Lu, Qian; Yang, Tingting; Wang, Tao; Yin, Xiaoxing (Frontiers in Endocrinology, 2022)
Background: Exenatide is a GLP1-R agonist that exhibits considerable interindividual variability in therapeutic efficacy. However, there is no evidence about the impact of genetic polymorphism in the PPARD on the therapeutic efficacy of exenatide. This research was aimed to explore the influence of PPARD gene polymorphism on the therapeutic effect of exenatide, and to identify the potential mechanism futher. Methods: A total of 300 patients with T2DM and 200 control subjects were enrolled to identify PPARD rs2016520 and rs3777744 genotypes. A prospective clinical study was used to collect clinical indicators and peripheral blood of T2DM patients treated with exenatide monotherapy for 6 months. The SNaPshot method was used to identify PPARD rs2016520 and rs3777744 genotypes, and then we performed correlation analysis between PPARD gene polymorphism and the efficacy of exenatide, and conducted multiple linear regression analysis of factors affecting the therapeutic effect of exenatide. HepG2 cells were incubated with exenatide in the absence or presence of a PPARδ agonist or the siPPARδ plasmid, after which the levels of GLP1-R and the ratio of glucose uptake were determined. Results: After 6 months exenatide monotherapy, we observed that homeostasis model assessment for insulin resistance (HOMA-IR) levels of the subjects with at least one C allele of the PPARD rs2016520 were significantly lower than those with the TT genotype, which suggested that the PPARD rs2016520 TT genotype conferred the poor exenatide response through a reduction of insulin resistance, as measured by HOMA-IR. The carriers of G alleles at rs3777744 exhibited higher levels of in waist to hip ratio (WHR), fasting plasma glucose (FPG), hemoglobin A1c (HbA1c) and HOMA-IR compared to individuals with the AA genotype following 6 months of exenatide treatment, potentially accounting for the lower failure rate of exenatide therapy among the AA homozygotes. In an insulin resistant HepG2 cell model, the PPARδ agonists enhanced exenatide efficacy on insulin resistance, with the expression of GLP1-R being up-regulated markedly. Conclusion: These data suggest that the PPARD rs2016520 and rs3777744 polymorphisms are associated with exenatide monotherapy efficacy, due to the pivotal role of PPARδ in regulating insulin resistance through affecting the expression of GLP1-R.